PENGARUH PENGGUNAAN BAHAN AJAR BERBASIS QUIZIZZ TERHADAP KETERAMPILAN MENULIS TEKS LAPORAN HASIL OBSERVASI - Tia Hafiza Nadeak; Riris Nurkholidah Rambe (Universitas Negeri Makassar, 2024)
This study aims to determine the effect of Quizizzebased teaching materials on the writing skills of observation report texts of grade VII YPI Annur Prima students. This type of research applies a quantitative approach with a quasi-experiment research method. The population was 40 students and the sample size was report text. Data analysis techniques in this study used quantitative analysis in the form of descriptive and inferential statistical analysis. The results showed that there was an influence on the writing results of the experimental group using Quizizz-based teaching materials with the control group that only used conventional learning.20 students, namely class VII C as the experimental class and 20 students from class VII B as the control class. The instrument used to collect data on student learning outcomes is a test of writing observation.